A new species of the genus Stachorutes Dallai, 1973 from China (Collembola, Neanuridae) - Gao, Yan; Yin, Wenying (Zootaxa, 2007)
The genus Stachorutes of the subfamily Pseudachorutinae was established by Dallai (1973) based on the type species Stachorutes dematteisi by the character of reduced number of eyes. Thibaud and Palacios-Vargas (2000) redefined the genus as below: Small species with the appearance of Pseudachorutes; antennal segment IV with simple apical bulb, 5 or 6 thick cylindrical sensilla and one microsensillum; mandible with 2–3 large teeth; maxilla simple, styletiform; eyes less than 8+8; postantennal organ with 4 to 11 vesicles, never moruliform; tibiotarsi without clear clavate tenent hairs; unguis without teeth and unguiculus; ventral tube with 4+4 setae; sensillar formula of the body 022/11111; tenaculum with 2 or 3 teeth; furcula reduced; dens with 3 to 6 setae; mucro absent or very small, fused to dens; anal spines absent.